2015
DOI: 10.1097/opx.0000000000000723
|View full text |Cite
|
Sign up to set email alerts
|

Pupil Diameter Changes in High Myopes after Collamer Lens Implantation

Abstract: PurposeTo observe the changes in pupil size under photopic and scotopic conditions after Implantable Collamer Lens (ICL) implantations in eyes with high myopia.MethodsThe ICL was implanted in 90 eyes belonging to 45 patients with high myopia. Photopic pupil diameters, scotopic pupil diameters, anterior chamber depths, and ICL vaults were examined at the preoperative, postoperative 1-month, and postoperative 3-month stages. The preoperative and postoperative photopic pupil diameters and scotopic pupil diameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 26 publications
(19 reference statements)
4
13
3
Order By: Relevance
“…Although the change was statistically insignificant, it is worth mentioning that the p value was 0.062, which means it was close to the significance. This was different from results of previous studies [ 13 , 14 ], where a significant reduction in PD was observed both 1 and 3 months after ICL implantation. Li and associates [ 13 ] attributed this reduction to the contact between the iris and ICL, which limits postoperative pupil movements, as they found a significant correlation between lower degrees of myopia and decreased size of the pupil.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although the change was statistically insignificant, it is worth mentioning that the p value was 0.062, which means it was close to the significance. This was different from results of previous studies [ 13 , 14 ], where a significant reduction in PD was observed both 1 and 3 months after ICL implantation. Li and associates [ 13 ] attributed this reduction to the contact between the iris and ICL, which limits postoperative pupil movements, as they found a significant correlation between lower degrees of myopia and decreased size of the pupil.…”
Section: Discussioncontrasting
confidence: 99%
“…This was different from results of previous studies [ 13 , 14 ], where a significant reduction in PD was observed both 1 and 3 months after ICL implantation. Li and associates [ 13 ] attributed this reduction to the contact between the iris and ICL, which limits postoperative pupil movements, as they found a significant correlation between lower degrees of myopia and decreased size of the pupil. Our results were different perhaps because our patients had higher degrees of myopia as mean SE was −16.91 ± 2.37 D in our study, while it was −12.50 ± 4.28 in their study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Reductions in postoperative contraction amplitude, contraction velocity, and dilation velocity were observed in this study. The changes in contraction amplitude were consistent with previous studies [8, 9]. In terms of velocity, Totsuka et al found no significant changes in maximum constriction velocity or maximum dilation velocity, between preoperative measurements and measurements at 1, 3, and 6 months after ICL V4c implantation [21].…”
Section: Discussionsupporting
confidence: 90%
“…Kamiya et al [23] found that pupil diameters of patients aged 35.7 ± 12.0 years were transiently reduced at 1 day after ICL implantation, then returned to preoperative levels at 1 week after implantation and subsequently remained stable. Two studies in patients who were less than 30 years of age found that the recovery time was more than 3 months [7, 8]. Thus, the occurrence of a reduced pupillary light response might be a short-term change.…”
Section: Discussionmentioning
confidence: 99%